Perinatal outcome of severe obstetric complications: findings of a 10-year hospital-based surveillance study in Italy - Zanconato G; Cavaliere E; Mariotto O; Zatti N (Dove Medical Press, 2019)
Giovanni Zanconato,1 Elena Cavaliere,2 Olga Mariotto,1 Nicoletta Zatti11Department of Surgical Sciences, Odontostomatology and Maternal and Child Health, University of Verona, Verona, Italy; 2U.O. di Ginecologia e Ostetricia, Azienda Ospedaliera Universitaria Integrata of Verona, Verona, ItalyCorrespondence: Giovanni ZanconatoU.O. di Ginecologia e Ostetricia, Ospedale Donna Bambino, Polo Ospedaliero di Borgo Trento, Verona 37121, ItalyFax +39 045 802 7481Email giovanni.zanconato@univr.itObjective: To assess incidence and clinical patterns of severe maternal morbidities related to pregnancy. To determine associated feto-maternal outcomes and economic costs for the institution.Methods: Observational study in a tertiary care Italian public hospital during a 10-year period. To identify severe obstetric complications, the following management-based criteria were adopted: need for intensive care unit admission, blood transfusion ≥5 units, emergency peripartum hysterectomy/laparotomy and arterial embolization. Impact of severe obstetric complications on facility resources was estimated considering length of hospital stay, need for additional surgery and transfusion.Results: A total of 151 cases were identified, most frequent obstetric morbidities being major obstetric hemorrhage (50.3%) and hypertensive disorders (19.2%). Pre-term birth, caesarean section and sub-saharan African origin were factors significantly associated with severe morbidity. Maternal mortality and maternal mortality to morbidity ratios were 17 per 100,000 live births and 3:151, respectively. Stillbirth rate was 4.4%. Massive use of blood products and prolonged admissions concurred to increase hospital expenditures.Conclusion: Institutional severe maternal morbidities may be effectively monitored by implementing a surveillance program and selecting a combination of management-based criteria which define the extremely morbid cases. Focusing on causes and risk factors associated with adverse obstetric situations has the potential to improve quality of care, prevent maternal life-threatening complications and perinatal mortality, reduce hospital expenditures.Keywords: maternal near miss, organ dysfunction, severe obstetric morbidity, intensive care unit